Profile of Selected Physical Fitness Variables of Weight Category of -56 Kg to -60 Kg of Top-Class Indian Judokas - Verma, Arun; Saxena, Vikas (Stallion Journal for Multidisciplinary Associated Research Studies, 2022)
The purpose of the study was to prepare the profile of selected Physical fitness variables of 20 athletes who had competed at the national level comprised only male players from Madhya Pradesh who were between the ages of 18 and 25 and who were residents of Madhya Pradesh. Each of these athletes was a native of the Indian state of Madhya Pradesh. All the physical fitness variables measured with their respective standard test. Results of the study showed that in physical fitness variables back strength was lowest in -56 kg to -60 kg. Shoulder strength was lowest in -56 kg to -60 kg. Grip strength lowest in -56 kg to -60 kg. Leg Explosive Strength lowest in -56 kg to -60 kg. Speed was maximum in weight category-56 kg to -60 kg. Speed Endurance was maximum in weight category -56 kg to -60 kg. Agility was maximum in weight category -56 kg to -60 kg. Thus, Physical fitness is the core of sports. Physical fitness of a player is influenced by age, sex, diet and condition. Legitimate co-appointment of these elements can lead a player to the pinnacle execution. In combative games like judo physical fitness assumes an essential job.